Quality characteristics of low fat paneer developed from yak milk - KANDEEPAN, G; SANGMA, S; PAUL, V; JAYKUMAR, S (The Indian Journal of Animal Sciences, 2010)
Yak milk paneer is a highly relished luxurious product in yak rearing tracts. Traditional full fat yak milk paneer has very high fat content, moderately desirable body and texture and poor microbial quality. Growing health concern of consuming fat rich products offers scope to develop low fat paneer from yak milk. Therefore, a study was undertaken to develop low fat paneer from yak milk and to evaluate its quality attributes. The results indicated that optimization of fat at 1% level increased the levels of SNF, protein and density in yak milk. The moisture and ash content increased but yield and fat content decreased in paneer prepared from low fat yak milk. Low fat paneer showed a decrease in total mesophilic and yeast and mold count. It is concluded that a well acceptable low fat paneer with improved body and texture can be prepared with 1% fat in yak milk.